The process of family disintegration in Black Brant - Jones, Dorothy M; Jones, Dorothy M (Wildfowl, 1966)
A study of family behaviour in Black Brant in Izembek Bay, Alaska, in the fall of 1965 revealed that family groups arriving in migration from the nesting grounds disintegrate before resuming the migration southward. Birds arrived in flocks of non-breeders or of family groups and after family disintegration departed in flocks of random mixture.